2021
DOI: 10.1111/ppc.12918
|View full text |Cite
|
Sign up to set email alerts
|

The aggressive patient experiences of healthcare professionals exposed to physical violence in a psychiatric clinic: A phenomenological study*

Abstract: Purpose This study investigated the experiences of healthcare professionals, exposed to physical violence, related to aggressive patients at a psychiatry service. Design and Methods The qualitative study sample consisted of a total of 21 healthcare professionals. The data were collected through in‐depth interviews. An inductive qualitative content analysis was used to analyze the data. Findings Three themes, the effects of warning signs of violence, clinical management of violence, and effects of violence, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Another study conducted by Ayhan, et al [12] in a psychiatric setting found poor management of violence. There was a lack of confidence in their de-escalation skills, and helplessness seemed to emerge, making the participants feel the only option left was physically and chemically restraining the violent perpetrator.…”
Section: Implementation Of Trainingmentioning
confidence: 93%
“…Another study conducted by Ayhan, et al [12] in a psychiatric setting found poor management of violence. There was a lack of confidence in their de-escalation skills, and helplessness seemed to emerge, making the participants feel the only option left was physically and chemically restraining the violent perpetrator.…”
Section: Implementation Of Trainingmentioning
confidence: 93%
“…Although highly relevant, concentrating solely on patient characteristics to assess the risk of aggressive behavior is a one‐sided strategy. The role of nursing characteristics can provide further insight in the risk or aggressive behavior (Ayhan et al, 2021 ; Lamanna et al, 2016 ; Weltens et al, 2021 ). Salzmann‐Erikson and Yifter ( 2019 ) found that nurses with longer employment encountered less aggressive patient behavior during their shift.…”
Section: Introductionmentioning
confidence: 99%